Kebijakan Dividen dalam Memoderasi Profitabilitas, Likuiditas, Leverage, Firm Size, dan Free Cash Flow Terhadap Nilai Perusahaan - Andini Rida Palupi; Dimas Emha Amir Fikri Anas; Ati Retna Sari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This research aims to examine the impact profitability, liquidity, leverage, firm size, and free cash flow on firm value, with dividend policy serving as a moderating variable specifically for basic materials companies listed on the Indonesia Stock Exchange during the period from 2019 to 2023. A quantitative approach with causal-associative design is applied in this study. Secondary data, sourced from annual financial statements, is used, and purposive sampling result in a sample of 11 companies and 55 observations. Data analysis is performed using Partial Least Squares (PLS) through SmartPLS4. The findings reveal that profitability, liquidity, leverage, and free cash flow do not significantly influence firm value. However, firm size is found to have a significant effect on firm value. Additionally, dividend policy does not moderate the relationship between the independent variables and firm value. These result suggest that firm value is primarily determined by company size rather than financial performance indicators. This study contributes by emphasizing the limited role of financial ratios and dividend policy in explaining firm value, highlighting the need to consider additional fctors outside the scope of the current research model.